ASSESSING THE OTTO OPTION: THORIUM-CYCLE EXPERIMENTAL POWER REACTOR SPENT FUEL CHARACTERISTICS - R. Andika Putra Dwijayanto; Ihda Husnayani; Zuhair Zuhair (BATAN, 2020)
Two main refuelling option considered for use in a High Temperature Gas-cooled Reactor (HTGR) are multi-pass and once through-then-out (OTTO) cycle. The former possesses superiority in term of fuel utilisation whilst the latter is considered better in term of system simplicity. HTGR-based Experimental Power Reactor (Reaktor Daya Eksperimental/RDE) is supposed to adopt multi-pass refuelling scheme. However, OTTO-scheme shall also be considered for the simplicity it offers and thus potentially lower cost. Due to different neutronic and burnup profile between the two, the resulting spent fuel characteristic is also different and possibly requires different handling mechanism. This paper assesses the characteristics of OTTO-scheme RDE spent fuel using thorium fuel cycle. The assessment is performed employing ORIGEN2.1 code. At day 30 of cooling after determined end-of-cycle (EOC), each spent fuel yields 234.9 Curies of radioactivity, emitting 66.26 neutrons/second, 1x1013 photons/second, and releasing 0.7675 watts of decay heat. These numbers must be taken into consideration regarding spent fuel management and spent fuel cask design. Tl-208 isotope characteristics, whose existence is unique to thorium fuel cycle, were also determined. It is found to be yielding 3.42x10-3 Curie of radioactivity and releasing 1.2x108 photons/second at its peak. Understanding its high-energy gamma release, proper radiation protection mechanism must be implemented.